1999
DOI: 10.1210/endo.140.6.6759
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Factor-1 Interacts with a Gonadotrope-Specific Element within the First Exon of the Human Gonadotropin-Releasing Hormone Receptor Gene to Mediate Gonadotrope-Specific Expression*

Abstract: GnRH plays a pivotal role in regulating human reproductive functions. This hypothalamic peptide interacts with its receptor (GnRHR) on the pituitary gonadotropes to trigger the secretion of gonadotropins, which, in turn, regulates the release of sex steroids from the gonads. In light of the importance of GnRHR, the molecular mechanisms underlying the transcriptional regulation of the human GnRHR (hGnRHR) gene become a key issue in understanding human reproduction. In this report, the possible involvement of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 31 publications
1
28
1
1
Order By: Relevance
“…In addition, some SF-1 positive cells at E15.5 and E18 do not express the transgene. This contrasts with data derived from transient transfection studies, which have demonstrated a pivotal role for SF-1 in mouse, rat, and human GnRH-R promoter activity (9,11,12,40). Our in vivo data indicate that signals other than SF-1 are necessary for turning on the GnRH-R gene.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, some SF-1 positive cells at E15.5 and E18 do not express the transgene. This contrasts with data derived from transient transfection studies, which have demonstrated a pivotal role for SF-1 in mouse, rat, and human GnRH-R promoter activity (9,11,12,40). Our in vivo data indicate that signals other than SF-1 are necessary for turning on the GnRH-R gene.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, the interaction of SF-1 with a gonadotrope-specific element motif in the human gene has been shown to mediate gonadotrope-specific expression (10). Regarding the rat promoter, we and others have reported that full gonadotrope specific activity required a distal regulatory domain in addition to the SF-1 and AP-1 elements present in the proximal domain (7,8,11).…”
mentioning
confidence: 79%
“…NR5A1 is expressed in steroidogenic tissues (Honda et al, 1993; Ikeda et al, 1993; Morohashi et al, 1994; Parker and Schimmer, 1997; Ramayya et al, 1997; Morohashi, 1999), pituitary gonadotrophs (Barnhart and Mellon, 1994; Ingraham et al, 1994; Ngan et al, 1999), and neurons located at the dorsomedial portion of the ventromedial hypothalamus (VMH) (Ramayya et al, 1997; Morohashi et al, 1999). In developing embryos, Nr5a1 is expressed in the urogenital ridge, representing the first marker of gonadal and adrenal differentiation (Ikeda et al, 1994; Morohashi et al, 1995, 1999; Ramayya et al, 1997; Hanley et al, 1999, 2001).…”
Section: Introductionmentioning
confidence: 99%